БАЛЬМОНТ И ПОЛЬСКИЕ ПОЭТЫ: ДУХОВНАЯ ЛИРИКА ЮЛИУША СЛОВАЦКОГО - Певцов, Григорий (Acta Neophilologica, 2017)
This paper discusses some important aspects of creative relations between Konstantin Balmont and Polish poets as well as the particularities of translations of the works by an outstanding poet Juliusz Słowacki created by Balmont. Additionally, the article examines the sojourn of Balmont with his wife Yelena Tsvetkovskaya in Poland in 1927 (meetings and speeches given by the poet, the lecture tour of the major towns of the country).